Development of high-voltage negative ion based neutral beam injector for fusion devices. (27th September 2021) - Sotnikov, O.; Ivanov, A.; Belchenko, Yu.; Gorbovsky, A.; Deichuli, P.; Dranichnikov, A.; Emelev, I.; Kolmogorov, V.; Kondakov, A.; Sanin, A.; Shikhovtsev, I.
Abstract: A prototype of a powerful high-voltage neutral beam injector, based on acceleration of negative hydrogen ions and their neutralization, is under development at Budker Institute of Nuclear Physics (BINP). The design of the BINP high-voltage injector includes several innovative components, important for injector operation stability and overall efficiency. It includes a multi-aperture long-pulse surface-plasma negative ion source with thermostabilized grid, ithe magnetic system with concaved field lines in the ion-optic system (IOS) and the distributed cesium deposition system. The injector scheme incorporates a wide-aperture low-energy beam transport (LEBT) section, plasma target for negative ionneutralization, and recuperators of non-neutralized ions. Several test stands were constructed at BINP for injector component studies. This paper describes the results of experiments on negative ion beam production, transport through LEBT, ion acceleration to energy up to 240 keV and transport through the high voltage beam transport (HEBT) section to the distance ∼10 m from the source. The parameters of the transported beam, which were measured at several points along the beam line and at the beam dump calorimeter, are presented. The beam transport efficiency as a function of various ion source, LEBT and HEBT parameters is measured and compared with the calculated values. The results dof plasma neutralization target study are presented as well.